Perbedaan Pendapat Menurut Jumhur Ulama dan Abu Hanifah Terkait Nafkah Suami Miskin - Ali Ad Dhar; Ayu Hijrani Salamah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The husband's obligation to provide for his wife is one of the primary responsibilities in marriage, as regulated by various legal systems and religious values. However, challenges arise when a husband is in a state of economic poverty and unable to meet the family's basic needs. This article aims to explore how the concept of provision (nafkah) is applied in such situations from the perspectives of Islamic law, state law, and social norms. Based on a literature review, it is found that Islam provides flexibility for impoverished husbands to strive within their capacity, while emphasizing the importance of communication, mutual understanding, and cooperation between husband and wife. Furthermore, the responsibility to provide is not solely material but also includes emotional and spiritual aspects. This article also highlights the need for community and state support in creating social protection systems for impoverished families to ensure their welfare. Thus, the husband's responsibility to provide is not only viewed as an individual duty but also within the framework of collective responsibility.